2019
DOI: 10.1021/acsami.9b20707
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Functionalized DNA Origami for Targeted Codelivery of Antisense Oligonucleotides and Doxorubicin to Enhance Therapy in Drug-Resistant Cancer Cells

Abstract: Drug resistance is a major obstacle to the efficient therapy of drug-resistant cancer. To overcome this problem, we constructed a multifunctional DNA origami-based nanocarrier for codelivery of a chemotherapeutic drug (doxorubicin, Dox) and two different antisense oligonucleotides (ASOs; B-cell lymphoma 2 (Bcl2) and P-glycoprotein (P-gp)) into drug-resistant cancer cells for enhanced therapy. To increase the targeting ability of origami, staple strands with 5′-end extended MUC1 sequences were used in the prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 58 publications
1
102
0
Order By: Relevance
“…The effect of aggregation is most dramatic at poorly optimized conditions (2 mM DOX, pH 8.0, and 12.5 mM MgCl 2 ), but it can affect the sample composition in smaller amounts also at lower DOX concentrations and other buffer conditions, requiring efficient purification of the aggregates from the sample. Here, we used the centrifugation method (32,34,36,39) for separating DOX-loaded DONs from free DOX, and found that its use as a purification method is highly questionable, as the major component of the formed precipitate is aggregated DOX. This in turn may lead to a mis-identification of aggregated DOX as DOX-DON complexes, and carry major implications on the validity of conclusions made about the therapeutic efficiency of the prepared DOX-loaded DONs.…”
Section: Dox Loading and Choice Of Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of aggregation is most dramatic at poorly optimized conditions (2 mM DOX, pH 8.0, and 12.5 mM MgCl 2 ), but it can affect the sample composition in smaller amounts also at lower DOX concentrations and other buffer conditions, requiring efficient purification of the aggregates from the sample. Here, we used the centrifugation method (32,34,36,39) for separating DOX-loaded DONs from free DOX, and found that its use as a purification method is highly questionable, as the major component of the formed precipitate is aggregated DOX. This in turn may lead to a mis-identification of aggregated DOX as DOX-DON complexes, and carry major implications on the validity of conclusions made about the therapeutic efficiency of the prepared DOX-loaded DONs.…”
Section: Dox Loading and Choice Of Conditionsmentioning
confidence: 99%
“…Its main mechanism of action takes place via type IIA DNA topoisomerase inhibition, but it also affects multiple other cellular processes through DNA intercalation and generation of reactive oxygen species (ROS) (32). The therapeutic potency of various DOX-loaded DNA origami nanostructures (DONs) has been demonstrated using in vitro and in vivo models in a number of reports (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
“…Another protein, B-cell lymphoma 2 (Bcl2), acting as an anti-apoptotic factor on the mitochondrial membrane, also contributes to the drug resistance through inhibiting cell death ( 88 ). Therefore, Pan et al constructed a multifunctional DNA origami-based carrier, a promising candidate for tumor imaging, with both doxorubicin and two different antisense oligonucleotides (ASOs) that target P-gp and Bcl2, for enhancing efficacy of treatment ( 16 ). This strategy reveals the potential of combining chemotherapy and oligonucleotides in aptamer-based targeted therapy.…”
Section: Aptamers-based Research On Immune Diseasesmentioning
confidence: 99%
“…In the context of multiple myeloma (MM) activities, a modified RNA aptamer, apt69.T, was synthesized to target B cell maturation antigen (BCMA), a critical factor in promoting plasma cells (PCs) survival, to inhibit MM activities (13). In addition, B cell antigens including CD19 and CD20 that are overexpressed on various B cell malignancies, are also suitable markers for aptamer targeting (14)(15)(16). Further, due to the cellbinding and internalization properties, a framework combining aptamers and therapeutic agents could be used for the therapeutic strategy for immune diseases (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…[2] For instance, FNAs that co-delivered doxorubicin and B-cell lymphoma 2 (Bcl2) and P-glycoprotein (P-gp) antisense oligonucleotides demonstrated enhanced efficacy against DOI: 10.1002/adtp.202000041 drug-resistant cancer cells. [3] Likewise, tetrahedral FNA effectively delivered DNAzyme Dz13 into the cytoplasm to cleave c-Jun mRNA and inhibited the growth of squamous cell carcinoma. [4] In another example, aptamer-conjugated FNA stimulated internalization and digestion of HER2 membrane protein, resulting in apoptosis and growth arrest in breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%